Bragg grating-based Fabry–Perot interferometer fabricated in a polymer fiber for sensing with improved resolution. (9th December 2016) - Statkiewicz-Barabach, G; Mergo, P; Urbanczyk, W
Abstract: We demonstrate for the first time a Bragg grating-based Fabry–Perot interferometer (FPI) fabricated in the polymer fiber with a core made of PMMA/PS copolymer and pure PMMA cladding. The FPI was formed by two gratings with the same Bragg wavelength, λ B  = 1312 nm, separated by a small gap. The FP cavity was created directly during the grating inscription process by placing a narrow blocking aperture, in the center of the UV beam. Good long-term stability was achieved by fabricating the gratings of type II with long irradiation time (8 min). By choosing an appropriate width of the blocking aperture, we could control the number and the width of interference fringes visible in the grating's reflection spectrum. Sharp fringes were obtained, of 3 dB width within the range of 50–100 pm, allowing for a significant increase in measurement resolution compared to direct interrogation of a single grating. The proposed interferometer was tested in measurements of strain and temperature in the range of 0–20 mstrain and 20 °C–70 °C, showing the sensitivity of 1.074 nm mstrain −1 and −25.1 pm °C −1, respectively.